Polymer-coated modified heavy calcium carbonate composite particle as well as preparation method and application thereof
By preparing polymer-coated modified heavy calcium carbonate composite particles, the problem of poor compatibility between heavy calcium carbonate and PVC matrix is solved, the mechanical properties and dispersion of PVC edge sealing strips are improved, and the production cost is reduced.
Patent Information
- Application Number
- CN202411284478.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The number of hydroxyl groups on the surface of heavy calcium carbonate is small and hydrophilic and oleophobic, which leads to an increase in the production cost of PVC edge strip material and poor interface compatibility with the PVC matrix, making it difficult to achieve toughening and enhancement effects.
The preparation method of polymer-coated modified heavy calcium carbonate composite particles is used, and the heavy calcium carbonate is mixed with NaOH and Na2CO3, and then the silane coupling agent, sodium dodecyl sulfate and other compounds are added for hydrolysis and grafting. Reactions to form composite particles with modified surfaces, improving their compatibility and mechanical properties with PVC.
The dispersion and activation of composite particles are improved, the oil absorption rate is reduced, the tensile strength, bending strength and impact strength of PVC plastic edge sealing strips are enhanced, and the production cost is reduced.
Smart Images

Figure BDA0005042726550000061 
Figure BDA0005042726550000091 
Figure HDA0005042726560000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic powders, and particularly relates to polymer-coated modified heavy calcium carbonate composite particles, and a preparation method and application thereof. Background Art
[0002] With the continuous development of the country, the continuous improvement of people's living standards, and the growing demand for material quality, the application requirements of PVC edge banding in furniture, office equipment, kitchen utensils, teaching facilities and civil laboratories are also gradually increasing. The basic components of PVC edge banding include polyvinyl chloride resin, calcium carbonate powder and various auxiliary ingredients, such as stabilizers, dioctyl phthalate (DOP) oil, acrylate copolymer (ACR), lubricants, pigment powders, antioxidants, etc. Calcium carbonate is the main inorganic filler in the production of PVC edge banding.
[0003] Calcium carbonate (CaCO 3 ) As one of the most widely used inorganic mineral functional fillers, especially ground calcium carbonate (GCC), the main component of which is CaCO3, it is made by mechanically crushing natural calcium carbonate ore (such as limestone, chalk or marble). GCC has the advantages of low cost, high whiteness and environmental friendliness. Compared with precipitated calcium carbonate (PCC), its production cost is relatively low and it is widely used in various fields such as plastics, coatings, papermaking, rubber, etc.
[0004] However, heavy calcium carbonate has a small number of hydroxyl groups on its surface, is hydrophilic and oleophobic, and absorbs more plasticizers, which increases the production cost of PVC edge banding materials. Since the composite materials prepared from heavy calcium carbonate fillers and PVC have poor interface compatibility and weak bonding, they can only play the role of increment and filling, and it is difficult to achieve the effect of strengthening or toughening. In order to overcome these problems, it is usually necessary to surface modify the heavy calcium carbonate filler to enhance the compatibility between the GCC filler and the PVC matrix. At present, the most commonly used surface modifiers for GCC are silane coupling agents, titanate coupling agents, aluminate coupling agents, stearic acid, etc., which form a coating layer on the surface of heavy calcium carbonate powder particles, which has poor stability and is difficult to achieve the purpose of toughening and strengthening at the same time. Summary of the invention
[0005] In order to solve the above-mentioned shortcomings and deficiencies in the prior art, the primary purpose of the present invention is to provide a method for preparing polymer-coated modified heavy calcium carbonate composite particles.
[0006] Another object of the present invention is to provide a polymer-coated modified heavy calcium carbonate composite particle prepared by the above-mentioned preparation method; the composite particle has good dispersibility, low oil absorption rate and high activation degree.
[0007] Another object of the present invention is to provide an application of the above polymer-coated modified heavy calcium carbonate composite particles.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing polymer-coated modified heavy calcium carbonate composite particles comprises the following steps:
[0010] (1) mixing heavy calcium carbonate with a mixed solution of NaOH and Na2CO3, wherein the solid content of the heavy calcium carbonate is 10% to 30%, stirring at room temperature for 2 hours, filtering, washing with distilled water, and then drying in a vacuum drying oven to obtain surface hydroxylated heavy calcium carbonate;
[0011] (2) hydrolyzing the silane coupling agent KH-570 in a 95% by volume ethanol solution at room temperature until the solution becomes clear to obtain a silane coupling agent KH-570 hydrolyzate; adding the silane coupling agent KH-570 hydrolyzate to the surface hydroxylated heavy calcium carbonate obtained in step (1), placing the mixture in an oil bath, continuously stirring, condensing and refluxing for 3 hours, filtering with suction, and drying the filter cake to obtain a heavy calcium carbonate modified with the silane coupling agent KH-570, namely, KH570-OH-GCC;
[0012] (3) adding sodium dodecyl sulfate (SDS), deionized water and KH570-OH-GCC obtained in step (2) in sequence; starting mechanical stirring and ultrasonic dispersion, adjusting the pH to 8-10 with NaOH solution, heating to 75° C. while introducing nitrogen for protection, adding initiator potassium persulfate (KPS) for reaction; adding a mixed solution of butyl acrylate (BA) and ethylene glycol dimethacrylate (EGDMA) dropwise, and reacting for 2 h after the addition is complete; adding an emulsifier and continuing stirring, adding a mixed solution of methyl methacrylate (MMA) and allyl methacrylate (AMA grafting agent), and reacting for 2.5 h after the addition is complete, cooling, filtering, and drying to obtain polymer-coated modified heavy calcium carbonate composite particles (denoted as M-GCC).
[0013] The particle size of the heavy calcium carbonate in step (1) is 2000-3000 mesh; the concentration of NaOH in the mixed solution of NaOH and Na2CO3 is 1.00 mol / L, and the concentration of Na2CO3 is 0.1 mol / L; the solid content of the heavy calcium carbonate is 10%.
[0014] The amount of the silane coupling agent KH-570 used in step (2) is 5% to 20% of the mass of the surface hydroxylated heavy calcium carbonate.
[0015] In step (3), the amount of sodium dodecyl sulfate is 0.5% to 1% of the mass of KH570-OH-GCC; the amount of potassium persulfate is 0.2% to 1% of the mass of KH570-OH-GCC; the amount of butyl acrylate is 10% to 30% of the mass of KH570-OH-GCC, the amount of ethylene glycol dimethacrylate is 0.5% to 1% of the mass of KH570-OH-GCC; the amount of methyl methacrylate is 10% to 30% of the mass of KH570-OH-GCC, and the amount of allyl methacrylate is 0.5% to 1% of the mass of KH570-OH-GCC.
[0016] A polymer-coated modified heavy calcium carbonate composite particle prepared by the above-mentioned preparation method.
[0017] The application of the above-mentioned polymer-coated modified heavy calcium carbonate composite particles in the preparation of PVC plastic edge banding strips, the PVC plastic edge banding strips are prepared according to the following method: 100 parts by mass of PVC resin, 5-20 parts by mass of polymer-coated modified heavy calcium carbonate composite particles, 7 parts by mass of DOA, 5 parts by mass of ACR, 2 parts by mass of calcium zinc stabilizer R660 and 1 part by mass of composite lubricant are mixed by dry stirring at 90-130°C for 5-30 minutes; a twin-screw granulator is used for extrusion granulation, the set temperature from the hopper to the die head is 160-200°C, and the screw speed is 100rpm; then the material is cooled in a water tank and granulated into particles with a length of 2-3mm, and the particles are placed in an oven at 80°C for drying for 6 hours; then an injection molding machine is used for injection molding, the temperature from the hopper to the injection port is set to 160-200°C, and the mold temperature is 40-60°C.
[0018] The amount of the polymer-coated modified heavy calcium carbonate composite particles is 15 parts by weight.
[0019] The composite lubricant includes PE wax and OP-10.
[0020] The PVC resin is a PVC material with a model of SG-1000.
[0021] In the formula of PVC plastic edge banding, PVC is the main ingredient in the formula, which directly provides the main function of the product; polymer-coated modified heavy calcium carbonate composite particles are the filler system, which improves the dimensional stability of the product and increases the hardness and mechanical properties of the product, while reducing costs; DOA is a plasticizer, which gives PVC good shaping and reduces processing temperature; ACR mainly improves product toughness and enhances impact resistance; calcium zinc stabilizer is used to improve thermal stability; composite lubricant is a lubricating system that increases fluidity and improves processing performance. The edge banding substrate is made through mixing, granulation, and extrusion molding.
[0022] Compared with the prior art, the present invention has the following advantages and effects:
[0023] (1) The polymer-coated modified heavy calcium carbonate composite particles prepared by the present invention have good dispersibility in liquid paraffin. The present invention can make the surface of the modified heavy calcium carbonate particles easily wetted and dispersed in the liquid paraffin.
[0024] (2) The polymer-coated modified heavy calcium carbonate composite particles prepared by the present invention have good activation, low absorption rate of DOP plasticizer, hydrophobic surface, and good compatibility with PVC resin; the water contact angle of the polymer-coated modified composite particles obtained by the present invention reaches 115.4° (the water contact angle of heavy calcium carbonate is 0), the activation degree reaches 96.2 (the activation degree of heavy calcium carbonate is 8.37), and the oil absorption rate is ≤12.8ml / 100g (the oil absorption rate of heavy calcium carbonate is ≤45.8ml / 100g). Butyl acrylate and methyl methacrylate coat the surface of heavy calcium carbonate, changing the hydrophilicity of calcium carbonate to lipophilicity, so that the calcium carbonate has better fluidity when mixed with PVC.
[0025] (3) The tensile strength, tensile modulus, flexural strength, flexural modulus and impact strength of the PVC plastic edge banding prepared by the present invention are improved as the filling amount of the polymer-coated modified heavy calcium carbonate composite particles increases. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a cross-sectional scanning electron microscope image of the polymer-coated modified heavy calcium carbonate-filled PVC composite material prepared in Example 6.
[0027] Figure 2 This is a cross-sectional scanning electron microscope image of the heavy calcium carbonate-filled PVC composite material prepared in Comparative Example 5. DETAILED DESCRIPTION
[0028] The present invention is further described below with reference to specific embodiments, but they should not be construed as limiting the present invention.
[0029] Example 1
[0030] This embodiment provides a polymer-coated modified heavy calcium carbonate-filled PVC composite material, which is prepared by the following method:
[0031] (1) Surface hydroxylation of heavy calcium carbonate
[0032] Mixing ground calcium carbonate (GCC, particle size of 2000-3000 mesh) with a mixed solution of NaOH and Na2CO3 (the concentration of NaOH in the mixed solution of NaOH and Na2CO3 is 1.00 mol / L, and the concentration of Na2CO3 is 0.1 mol / L), with a solid content of the ground calcium carbonate of 10%, stirring at room temperature for 2 hours, filtering, washing with distilled water, and then drying in a vacuum drying oven for 8 hours to obtain surface hydroxylated ground calcium carbonate (OH-GCC);
[0033] (2) Silane coupling agent KH-570 modified hydroxylated calcium
[0034] The silane coupling agent KH-570 is hydrolyzed in a 95% by volume ethanol solution at room temperature for 2 hours until the solution becomes clear to obtain a silane coupling agent KH-570 hydrolyzate; the silane coupling agent KH-570 hydrolyzate is added to the surface hydroxylated heavy calcium carbonate (OH-GCC) obtained in step (1), wherein the amount of the silane coupling agent KH-570 is 10% of the mass of the surface hydroxylated heavy calcium carbonate, and the mixture is placed in an oil bath, continuously stirred, condensed and refluxed for 3 hours, filtered, and the filter cake is dried at 60° C. to obtain a heavy calcium carbonate modified by the silane coupling agent KH-570, namely KH570-OH-GCC;
[0035] (3) Preparation of composite particles by emulsion method
[0036] In a three-necked flask, 0.9 g of sodium dodecyl sulfate (SDS), 300 mL of deionized water, and 100 g of KH570-OH-GCC obtained in step (2) were added in sequence; mechanical stirring was started for 30 min, ultrasonic dispersion was performed for 40 min, the pH was adjusted to 8-10 with NaOH solution, nitrogen was introduced for protection while heating to 75°C, 0.3 g of initiator potassium persulfate (KPS) was added and reacted for 30 min; 10 g of butyl acrylate (BA) and 0 .9g ethylene glycol dimethacrylate (EGDMA) mixed solution, react for 2h after addition; take about 1ml sample for characterization analysis; add 0.3g emulsifier and continue stirring for 10min, add 0.3g KPS, slowly and continuously add 10g methyl methacrylate (MMA) and 0.3g allyl methacrylate (AMA grafting agent) mixed solution, react for 2.5h after addition, cool, filter and dry to obtain polymer-coated modified heavy calcium carbonate composite particles (referred to as M-GCC). Weigh some of the dried samples of the composite particles, extract in acetone for 24h, and dry.
[0037] (4) Preparation of polymer-coated modified heavy calcium carbonate filled PVC composite material: (1) Use a high-speed mixer to mix: PVC resin (100phr), the above-obtained polymer-coated modified heavy calcium carbonate composite particles (15phr), calcium zinc stabilizer (2phr), ACR (5phr), composite lubricant (1phr), DOA (7phr) are uniformly mixed. (2) Use twin-screw granulation for granulation, the set temperature from the hopper to the die head is 160-200℃, and the screw speed is 100rpm; then the material is cooled in a water tank and granulated into 2-3mm long particles, and the particles are placed in an oven at 80℃ for 6h. (3) Use an injection molding machine to prepare specimens for mechanical property testing in accordance with ISO527, ISO178 and ISO179 standards. The temperature from the hopper to the injection port is set to 160-200℃, and the mold temperature is 40-60℃.
[0038] The contact angle, oil absorption rate and activation degree of the above GCC, OH-GCC, KH570-OH-GCC and M-GCC were tested. The results are shown in Table 1:
[0039] Table 1 Performance test of heavy calcium carbonate and its modified products
[0040]
[0041] Example 2
[0042] This embodiment also provides a polymer-coated modified heavy calcium carbonate-filled PVC composite material, which is different from Embodiment 1 only in that the added amounts of butyl acrylate and methyl methacrylate in step (3) are 20 g and 20 g, respectively.
[0043] Example 3
[0044] This embodiment also provides a polymer-coated modified heavy calcium carbonate-filled PVC composite material, which is different from Embodiment 1 only in that the added amounts of butyl acrylate and methyl methacrylate in step (3) are 30 g and 30 g, respectively.
[0045] Example 4
[0046] This embodiment also provides a polymer-coated modified heavy calcium carbonate filled PVC composite material, which is different from Example 2 only in that the amount of polymer-coated modified heavy calcium carbonate composite particles added in step (4) is 5 phr.
[0047] Example 5
[0048] This embodiment also provides a polymer-coated modified heavy calcium carbonate filled PVC composite material, which is different from Embodiment 2 only in that the amount of polymer-coated modified heavy calcium carbonate composite particles added in step (4) is 10 phr.
[0049] Example 6
[0050] This embodiment also provides a polymer-coated modified heavy calcium carbonate filled PVC composite material, which is different from the embodiment 2 only in that the amount of polymer-coated modified heavy calcium carbonate composite particles added in step (4) is 20 phr. The cross-sectional scanning electron micrograph of the obtained modified heavy calcium carbonate filled PVC composite material is as follows: Figure 1 As shown, Figure 1 The PVC composite material filled with polymer-coated modified heavy calcium carbonate has good compatibility, uniform dispersion, and no obvious void defects.
[0051] Comparative Example 1
[0052] The preparation process of the composite material is divided into mixing process, granulation and injection molding: (1) Use a high-speed mixer for mixing: PVC resin (100phr), calcium zinc stabilizer (2phr), ACR (5phr), processing aid (1.5phr), DOA (7phr) are uniformly mixed. (2) Use a twin-screw granulator for granulation, the set temperature from the hopper to the die is 160-200℃, the screw speed is 100rpm, and then the material is cooled in a water tank and granulated into 2-3mm long particles, and the particles are placed in an oven at 80℃ for 6h. (3) Use an injection molding machine to prepare specimens for mechanical property testing in accordance with ISO527, ISO178 and ISO179 standards; the temperature from the hopper to the injection port is set at 160-200℃, and the mold temperature is 40-60℃.
[0053] Comparative Example 2
[0054] This comparative example also provides a heavy calcium carbonate-filled PVC composite material, which is different from comparative example 1 only in that 5 phr of unmodified heavy calcium carbonate is added in the mixing step.
[0055] Comparative Example 3
[0056] This comparative example also provides a heavy calcium carbonate-filled PVC composite material, which is different from comparative example 1 only in that 10 phr of unmodified heavy calcium carbonate is added in the mixing step.
[0057] Comparative Example 4
[0058] This comparative example also provides a heavy calcium carbonate-filled PVC composite material, which is different from comparative example 1 only in that 15 phr of unmodified heavy calcium carbonate is added in the mixing step.
[0059] Comparative Example 5
[0060] This comparative example also provides a heavy calcium carbonate filled PVC composite material, which differs from comparative example 1 only in that 20 phr of unmodified heavy calcium carbonate is added in the mixing step. The cross-sectional scanning electron micrograph of the obtained heavy calcium carbonate filled PVC composite material is as follows: Figure 2 As shown, Figure 2 The PVC composites filled with unmodified heavy calcium carbonate have poor compatibility, resulting in a large number of void defects, which affect the mechanical properties of the composites.
[0061] Experimental example
[0062] The composite material strips obtained in Examples 1-6 and Comparative Examples 1-5 were used as experimental samples, and the tensile strength, elongation at break, flexural strength, flexural modulus, and notched impact strength of the composite material strips were tested in accordance with the standard methods of "GB / T1843-2008 Determination of Izod Impact Strength of Plastics", "GB / T 9341-2000 Test Method for Flexural Properties of Plastics", and "GB / T1040.1-2018 Determination of Tensile Properties of Plastics Part 1: General Principles". The results are shown in Table 2 below.
[0063] Table 2 Composite material performance test
[0064]
[0065] As can be seen from Table 1, by comparing Examples 1-3, it can be found that the mechanical properties of the modified heavy calcium carbonate in Example 2 when the amounts of butyl acrylate and methyl methacrylate used are 20% by mass of KH570-OH-GCC are better than those in Examples 1 and 3; at the same time, by comparing Examples 2, 4, 5, 6 with Comparative Examples 1, 2, 3, 4, 5, it can be seen that the mechanical properties of the PVC composite material filled with polymer-coated modified heavy calcium carbonate prepared by the present invention are improved.
[0066] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing polymer-coated modified heavy calcium carbonate composite particles, characterized in that The following steps are involved: (1) mixing heavy calcium carbonate with a mixed solution of NaOH and Na2CO3, wherein the solid content of the heavy calcium carbonate is 10% to 30%, stirring at room temperature for 2 hours, filtering, washing with distilled water, and then drying in a vacuum drying oven to obtain surface hydroxylated heavy calcium carbonate; (2) hydrolyzing the silane coupling agent KH-570 in a 95% by volume ethanol solution at room temperature until the solution becomes clear to obtain a silane coupling agent KH-570 hydrolyzate; adding the silane coupling agent KH-570 hydrolyzate to the surface hydroxylated heavy calcium carbonate obtained in step (1), placing the mixture in an oil bath, continuously stirring, condensing and refluxing for 3 hours, filtering with suction, and drying the filter cake to obtain a heavy calcium carbonate modified with the silane coupling agent KH-570, namely, KH570-OH-GCC; (3) adding sodium dodecyl sulfate, deionized water and KH570-OH-GCC obtained in step (2) in sequence; starting mechanical stirring and ultrasonic dispersion, adjusting the pH to 8-10 with NaOH solution, heating to 75° C. while introducing nitrogen for protection, adding initiator potassium persulfate for reaction; adding dropwise a mixture of butyl acrylate and ethylene glycol dimethacrylate, reacting for 2 h after the addition is complete; adding an emulsifier and continuing stirring, adding dropwise a mixture of methyl methacrylate and allyl methacrylate, reacting for 2.5 h after the addition is complete, cooling, filtering, and drying to obtain polymer-coated modified heavy calcium carbonate composite particles.
2. The method for preparing a polymer-coated modified heavy calcium carbonate composite particle according to claim 1, characterized in that: The particle size of the heavy calcium carbonate in step (1) is 2000-3000 mesh; the concentration of NaOH in the mixed solution of NaOH and Na2CO3 is 1.00 mol / L, and the concentration of Na2CO3 is 0.1 mol / L; the solid content of the heavy calcium carbonate is 10%.
3. The method for preparing a polymer-coated modified heavy calcium carbonate composite particle according to claim 1, characterized in that: The amount of the silane coupling agent KH-570 used in step (2) is 5% to 20% of the mass of the surface hydroxylated heavy calcium carbonate.
4. The method for preparing a polymer-coated modified heavy calcium carbonate composite particle according to claim 1, characterized in that: In step (3), the amount of sodium dodecyl sulfate is 0.5% to 1% of the mass of KH570-OH-GCC; the amount of potassium persulfate is 0.2% to 1% of the mass of KH570-OH-GCC; the amount of butyl acrylate is 10% to 30% of the mass of KH570-OH-GCC, the amount of ethylene glycol dimethacrylate is 0.5% to 1% of the mass of KH570-OH-GCC; the amount of methyl methacrylate is 10% to 30% of the mass of KH570-OH-GCC, and the amount of allyl methacrylate is 0.5% to 1% of the mass of KH570-OH-GCC.
5. A polymer-coated modified heavy calcium carbonate composite particle prepared by the preparation method according to any one of claims 1 to 4.
6. The use of the polymer-coated modified heavy calcium carbonate composite particles according to claim 5 in the preparation of PVC plastic edge banding strips, characterized in that: The PVC plastic edge banding strip is prepared according to the following method: 100 parts by mass of PVC resin, 5-20 parts by mass of polymer-coated modified heavy calcium carbonate composite particles, 7 parts by mass of DOA, 5 parts by mass of ACR, 2 parts by mass of calcium zinc stabilizer R660 and 1 part by mass of composite lubricant are mixed by dry stirring at 90-130° C. for 5-30 minutes; a twin-screw granulator is used for extrusion granulation, the set temperature from the hopper to the die head is 160-200° C., and the screw speed is 100 rpm; then the material is cooled in a water tank and granulated into particles with a length of 2-3 mm, and the particles are placed in an oven at 80° C. for drying for 6 hours; then an injection molding machine is used for injection molding, the temperature from the hopper to the injection port is set to 160-200° C., and the mold temperature is 40-60° C.
7. The use according to claim 6, characterized in that: The amount of the polymer-coated modified heavy calcium carbonate composite particles is 15 parts by weight.
8. The use according to claim 6, characterized in that: The composite lubricant includes PE wax and OP-10.
9. The use according to claim 6, characterized in that: The PVC resin is a PVC material with a model of SG-1000.
Citation Information
Patent Citations
Method for preparing hard polyvinyl chloride plastic toughening and reinforcing agent
CN101705022A
Modifier and application thereof, modified heavy calcium carbonate and preparation method and application thereof
CN112980052A
Light PVC (polyvinyl chloride) edge band and preparation method thereof
CN114044993A
Cited By
Preparation method of nano calcium carbonate for reinforcing rubber
CN120118538A
Stone-plastic floor and extrusion molding preparation method thereof
CN121424776A
